Service marketing managers’ level of realizing their instructional leadership roles: the applied example on city of Istanbul for the effect on level of business success and performance, - Korkmaz, M., Yücel, A. S., Aksoy, M., Cesim, T.D., Gümüş, S. (My University, 2014)
Today, manager and personnel profiles are continuously changing and developing. Managers and personnel in the field of service marketing should improve themselves in line with the continuous change and development. It is a non-negligible fact that managers undertake instructional leadership roles and they hereby provide their personnel and themselves an opportunity for sustainable training. The purpose of the study is to examine the attitudes and perceptions of managers working in different fields of service marketing for the continuous training of their personnel regarding performance, success and service quality. Moreover, the relation between training and marketing communication was analyzed within the scope of the research. In this context, a two-part questionnaire was applied to a total of randomly selected 950 managers from different service sectors in Istanbul. Data of the questionnaire were analyzed with PASW Statistic 18 package program. Following the reliability analysis, Cronbach’s alpha coefficient was found as 0.963. T test was used in independent samples and variables, and one-way ANOVA in comparisons with more than two groups. Besides Chi-Square tests were utilized for independency research. As a result of the research, it was concluded that 78% of the managers have stated continuous training as obligatory in service enterprises. It was observed that managers with high level of education are more conscious regarding providing training for personnel with the purpose of increasing the service quality. It was also determined that educational background of managers is an effective factor on evaluation of efficiency, performance and training and on believing that sales and marketing is the most important factor of communication.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Instructional Leadership; Service; Marketing